Caffeine in the fatigue retardment and improvement of performance - Ribas, Sabrina Ferreira (2012)
Introduction: Caffeine is one of the most used stimulant drugs in the world. This is an alkaloid belonging the methylxanthine family, whose formula is 1,3,7-trimethylxantine. When consumed in low dosages (2mg/Kg), caffeine increases wakefulness, decreases dorwsiness, relieves fatigue, increases the cathecolamine release, the heart rate, the diuresis and speeds up the metabolism. Due your several properties, your ergogenic effect has been studied a lot. It’s believed that this effect is associated with the possibility of caffeine powered the athletes performance, retarding the fatigue through mechanisms controlled by nervous system. Purpose: The purpose of this study was to review and discuss the related research about this subject in order to compare the effects of caffeine supplementation in different exercises, doses and used protocols. Conclusion: Caffeine has your ergogenic effect comproved in several exercises, with less effectiveness in high intensity and short term. The most potent dosage varies between 3-6mg/Kg. Its effects are better explained for the adenosine antagonism while other mechanisms are still contradictory. Non-users caffeine and high trained individuals present better results. Associated with carbohydrate it promotes increased performance when ingested during or post-exercise and combined with creatine, this last is impaired. Due the variety actions and tissues that it can act, caffeine needs more studies to improve the knowledge about your ergogenic potential.